THE INFLUENCE OF INFORMATION RECEIVED FROM FAMILY PLANNING OFFICERS ON THE CHOICE OF CONTRACEPTIVE DEVICES FOR WOMEN OF CHILDBEARING AGE (WUS) IN INDONESIA (ADVANCE ANALYSIS OF THE 2017 IDHS) - Desi, Desi; Abdullah, Asnawi; Arlianti, Nopa (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2022)
Background: Indonesia is ranked 4th in terms of its population using contraception, namely 65%. Based on 2017 Indonesian Health Demographic Survey (IDHS) data, 29% of women aged 15-49 who use certain contraceptive methods are informed about all the information and contraceptive tools used in modern Family Planning (KB) (57.2%), while 6.4% use traditional KB. The research aims  to determine the influence of information received on the choice of contraceptives among Women of Childbearing Age (WUS) in Indonesia. Method: This type of research is an analytical survey with a cross- sectional design. The population is all fertile women aged 15-49 years with a sample of 5.053 people. The sampling technique uses a primary sampling unit. Data analysis using the chi-square test and logistic regression test. The research results revealed that 56.02% used traditional family planning and 43.98% used modern family planning. Results: The analysis results showed that there was an influence of the information received on the choice of contraceptives (p=0.04 and OR=0.67). This means that the information received by WUS is 0.67 times more likely to choose a modern contraceptive method. Then there was an influence of the information received on the choice of contraceptives based on 34 provinces in Indonesia, obtained at p=0.001. Recommendation: It is recommended that the government, through the National Population and Family Planning Agency (BKKBN) continue to pay attention to the family planning program and ensure that every community implements the family planning program, as well as more extensively providing CIE (Communication, Information, and Education) for family planning.